Transcending the Impact of the Financial Crisis in the United Kingdom: Towards Plan F—a Feminist Economic Strategy. Issue 1 (February 2015) - Pearson, Ruth; Elson, Diane
This paper sets out a framework for understanding the impacts of the financial crisis and its aftermath that is based on the idea of three interacting spheres: finance, production and reproduction. All of these spheres are gendered and globalised. The gendered impact of the current crisis is discussed in terms of the impact on unemployment, employment protection and security, public sector services, social security benefits, pensions, and the real value of wages and living standards. Drawing on the analysis of the UK Women's Budget Group, the paper demonstrates that the biggest falls in disposable income as the result of austerity policies by the Conservative-led government since 2010 have been borne by the most vulnerable women—lone mothers, single women pensioners and single women without children. Working-age couples without children have been least affected. The paper then goes on to discuss what an alternative economic strategy, based on feminist political economy, might look like. It utilises the notion of the 'reproductive bargain', first developed to understand the transition in Cuba in the 1990s. It sets out a possible feminist economic strategy that insists on the incorporation of reproductive and care work into the analysis of alternative economic policies and links employment, wages and social security payments to public provisioning of trans-generational reproductive services. It suggests feasible strategies to finance the proposed Plan F—a feminist economic strategy.